Water Quality Assessment along With Pollution Sources of the Halda River - Islam, Md Shafiqul; Akbar, Ali; Akhtar, Aysha; Kibria, Md Manzoorul; Bhuyan, Md Simul (Journal of the Asiatic Society of Bangladesh, Science, 2017)
In the present study water quality assessment and land based sources of pollutants discharged into the Halda River through four major canals were investigated. The ranges of pH, DO, BOD, NO3-N, PO4-P, chloride and total alkalinity of the collected samples varied from 7.1-8.8, 3.35-4.70 mg/L, 0.055-5.0 mg/L, 0.12-3.1 mg/L, 0.06-0.16 mg/L, 8.4-69.30 mg/L and 73-220 mg/L, respectively. pH, DO, BOD showed significant changes at Mondakini Canal and Chengkhali Canal for monsoon, post-monsoon and winter (p <0.05) while chloride at Chengkali Canal for all seasons (p≤0.05). Moreover, TA, NO3-N and PO4-P exhibited significant variation in the concentration at Mondakini Canal, Madari Canal and Chengkali Canal for three seasons (p ≤0.05). River Pollution Index indicated that the water of river at Mondakini Canal, Madari Canal, Chengkhali Canal and Khondakia Canal varied from low to moderate pollution. According to the interviewers, the Halda River is being polluted due to industrial waste (53%), sewage contamination (20%), tobacco farming (13%), rubber dam (8%) and sand extraction (6%). Therefore, necessary preventive measures should be taken in order to control the unwise and unauthorized discharge of harmful pollutants into the Halda River for the better management and conservation of natural resources. Asiat. Soc. Bangladesh, Sci. 43(1): 61-70, June 2017